Towards integration of work and learning : strategies for connectivity and transformation - Stenström, Marja-Leena (Ed ); Tynjälä, Päivi (Ed ) (Springer, 2009)
Bibliogr. en fin de chap. Index
Keywords: EDUCATION; Employees Training of; Labor supply Effect of education on; Learning; Psychology of; Personnel Formation; Éducation et emploi